2011
DOI: 10.1111/j.1365-2826.2011.02179.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Localisation and Functional Implication of 26RFa Orthologue Peptide in the Brain of Zebra Finch (Taeniopygia guttata)

Abstract: Several neuropeptides with the C-terminal Arg-Phe-NH(2) (RFa) sequence have been identified in the hypothalamus of a variety of vertebrates. The present study was conducted to isolate novel RFa peptides from the zebra finch brain. Peptides were isolated by immunoaffinity purification using an antibody that recognises avian RFa peptides. The isolated peptide consisted of 25 amino acids with RFa at its C-terminus. The sequence was SGTLGNLAEEINGYNRRKGGFTFRFa. Alignment of the peptide with vertebrate 26RFa has rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Furthermore, in situ hybridization has shown specific expression of 26RFa/QRFP mRNA in the anterior hypothalamic nucleus in the chick brain, and the distribution of 26RFa/QRFP mRNA-containing perikarya clearly matches with that of 26RFa/QRFP-immunoreactive neurons (Ukena et al 2010). In the zebra finch, in situ hybridization analysis has revealed that expression of 26RFa/QRFP mRNA is localized to the anterior-medial hypothalamic area, the ventromedial nucleus of the hypothalamus, and the lateral hypothalamic area (Tobari et al 2011). These neuroanatomical data suggest that, in birds, 26RFa/QRFP produced in the hypothalamus participates in the control of feeding behavior, as shown previously in rodents (Chartrel et al 2006b, Do Régo et al 2006, Moriya et al 2006, Primeaux et al 2008.…”
Section: Non-mammalian Vertebratessupporting
confidence: 78%
See 4 more Smart Citations
“…Furthermore, in situ hybridization has shown specific expression of 26RFa/QRFP mRNA in the anterior hypothalamic nucleus in the chick brain, and the distribution of 26RFa/QRFP mRNA-containing perikarya clearly matches with that of 26RFa/QRFP-immunoreactive neurons (Ukena et al 2010). In the zebra finch, in situ hybridization analysis has revealed that expression of 26RFa/QRFP mRNA is localized to the anterior-medial hypothalamic area, the ventromedial nucleus of the hypothalamus, and the lateral hypothalamic area (Tobari et al 2011). These neuroanatomical data suggest that, in birds, 26RFa/QRFP produced in the hypothalamus participates in the control of feeding behavior, as shown previously in rodents (Chartrel et al 2006b, Do Régo et al 2006, Moriya et al 2006, Primeaux et al 2008.…”
Section: Non-mammalian Vertebratessupporting
confidence: 78%
“…Taken together, it appears that the C-terminal region of 26RFa/QRFP is responsible for the biological activity of the peptide. In addition to the chick data, it has been reported that central injection of 26RFa/QRFP in free-feeding male zebra finches stimulates food intake for 24 h, without a change in body mass (Tobari et al 2011). These results also indicate that 26RFa/QRFP exerts an orexigenic activity in various avian species.…”
Section: Non-mammalian Vertebratesmentioning
confidence: 64%
See 3 more Smart Citations